دراسة وتحليل دلالي في ألفاظ الأضداد في اللغة العربية / A semantic study and analysis of antonyms in Arabic Language - Benaissa , Mahdia (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2021)
مُلخَّص البحث: الأضداد ظاهرة من الظواهر اللّغوية التي أسهمت في نموّ الثروة اللّفظيّة والاتساع في التعبير عند العرب؛ وهي ضرب من المشترك اللّفظي الذي يتجلّى في احتواء اللّفظة الواحدة على معنيين مشتركين في النطق ولكنّهما متباينان في الدلالة، فإذا ما وصل هذا التباين حدَّ التناقض والتعاكس عُدَّت اللفظة في الأضداد. ومن اللغويون الذين سلكوا التضاد في جملة المشترك اللفظي نصّوا على أنه نوع أخصّ منه؛ نجد: سيبويه، وقُطرُب، والأصمعي، والمبرد، وابن الأنباري، وغيرهم. لقد اعتمد البحث في جانبه التطبيقي على عرض مجموعة من الألفاظ العربية و التي تعد من الأضداد ، فمن خلال المنهج الوصفي التحليلي قدمت وصفا نظريا لهذه الظاهرة ثم عرضت للألفاظ بالدراسة والتحليل وذلك بذكر مجموعة من الشواهد الشعرية أو من القرآن والسنة النّبويّة، ثم عرضت لأقوال العلماء في الظاهرة وموقفهم منها، وخلصت الدراسة إلى أنّ الأضداد من خصائص اللغة العربية التراثية المحافظة، وهي مصدر ثراء ماتع، ومثال حي على التنوع اللّغوي وغنى اللغة العربية، ومن أهم أسباب حدوثه اختلاف اللّهجات من قبيلة إلى أخرى في تقدير الدلالة اللغوية وتحديدها بدقة. الكلمات المفتاحية: الأضداد، المعاني، الاختلاف، اللغة العربية، تحليل. Abstract: Antonyms is a linguistic feature that contributed to the wealth of vocabulary and the expansion of expressions for the Arabs. It is a type of homonyms that are similar in pronunciation but different in their meanings. When the difference between the meanings contradicts each other, the words are antonyms. Some of the language scholars viewed that antonym is a more specific type of homonyms are: Sibawaih, Quṭrub, Al-Aṣmaʿī, Al-Mubarrad, Ibn Al-Anbāri and others. The practical aspect of the study is a presentation of a group of Arabic words that are considered as antonyms. The use of the descriptive and analytical method will give account on the theoretical aspect of antonym. Subsequently the antonyms will be analysed through referring them to the evidence from the poem, the Holy Qurān or the prophetic tradition as well as some of the views of the scholars on the subject. The study concludes that antonym is a preserved traditional feature of the Arabic language and its treasure. It is a living proof of the language diversity and the wealth of the Arabic language and that among its causes is the difference between the dialects of the tribes in detailing the exact meaning of those words. Keywords: Antonyms, meanings, differences, Arabic language, analysis. Abstrak: Antonim adalah ciri linguistik yang menyumbang kepada kekayaan perbendaharaan kata dan perluasan ungkapan untuk penutur bahasa Arab. Ia adalah sejenis homonim yang serupa dalam sebutan tetapi berbeza maknanya. Apabila perbezaan antara makna menjadi bercanggah antara satu sama lain, perkataan tersebut adalah antonim. Beberapa sarjana bahasa yang berpendapat bahawa antonim adalah jenis homonim yang lebih spesifik ialah seperti: Sibawaih, Quṭrub, Al-Aṣmaʿī, Al-Mubarrad, Ibn Al-Anbāri dan lain-lain. Aspek praktikal kajian ini akan memaparkan sekumpulan perkataan Arab yang dianggap sebagai antonim. Penggunaan kaedah deskriptif dan analitikal kajian ini akan menjelaskan aspek teori antonim. Seterusnya antonim akan dianalisis dengan merujuk kepada dalil dari syair, Al-Quran atau hadīts serta beberapa pandangan ulama tentang perkara tersebut. Kajian ini merumuskan bahawa antonim adalah ciri tradisional bahasa Arab yang merupakan khazanahnya yang terpelihara. Ia adalah bukti hidup kepelbagaian dan kekayaan bahasa Arab dan antara punca antonim itu ialah perbezaan dialek suku kaum dalam memperincikan maksud tepat untuk sesuatu perkataan tersebut. Kata kunci: Antonim, makna, perbezaan, bahasa Arab, analisis.